Analysis of Factors Associated with the Incidence of Child Sexual Violence - Rinna Fadilah; Rini Kundaryanti; Siti Syamsiah (Indonesian Journal of Global Health Research, 2025)
Sexual violence against children is a violation of human rights with long-term impacts on the physical, psychological, and social aspects of the child. This study aims to analyze the factors associated with the incidence of sexual violence against children and to identify the most dominant influencing factor using a sequential explanatory mixed methods approach.This study aimed to analyze factors associated with the incidence of child sexual violence and to identify the most dominant influencing factor using a sequential explanatory mixed-methods design. The quantitative phase involved 55 respondents consisting of child victims and their mothers, selected through total sampling at the Integrated Service Center for Women and Children Empowerment (P2TP2A) in South Tangerang City. Data were collected using structured questionnaires and analyzed using Spearman Rank correlation and logistic regression. The qualitative phase employed snowball sampling and in-depth interviews with victims, parents, and key informants, analyzed thematically. Quantitative results showed significant associations between sexual violence and child’s age (p=0.026), knowledge (p=0.000), media use (p=0.039), social environment (p=0.039), family income (p=0.048), and parenting style (p=0.049). Multivariate analysis identified child’s knowledge as the most dominant factor (OR=33.911; p=0.004). Qualitative findings reinforced that limited supervision, unsupportive environments, and poor parenting increase vulnerability. In conclusion, strengthening children’s knowledge, improving parental supervision, and fostering supportive social environments are essential strategies to prevent child sexual violence.